The concept of religious experience: A Qur'anic perspective - Shehu, Fatmir Mehdi (Faculty of Quranic and Sunnah Studies, Islamic Science Univerisity of Malaysia, 2009)
The misunderstanding of the concept of religious experience by the followers of world’s religions in general, and the followers of Islam in particular, have raised many problems in matters of each ones’ religious conviction. The divine style of the Qur’Én came as a challenge to humanity in general, and Arabs in particular. Religious experience found in the Qur’Énic verses reveals and reflects Allah’s Wisdom towards the communication of Islamic Creed and values that serve to guide humanity to the Straight Path. Indeed, the act of sending Qur’Én as a Divine Revelation to the Prophet (p.b.u.h.) is considered as the best example of religious experience lived and experienced by the Prophet (p.b.u.h.) himself. However, this article has attempted to study some selected Qur’Énic verses in which the religious experience is reflected. Besides, this article has discussed the genesis of religious experience and its universality; the main factors that help to understand the religious experience, i.e., religious conviction or faith and religious language; religious experience according to the context of the Qur’Énic verses, i.e., the religious experience of Prophet Muhammad (p.b.u.h.), and the religious experience of MËsÉ (p.b.u.h.), etc. This paper has concluded that the understanding of the concept of religious experience will help to enhance Muslims’ way of understanding of their Conviction in particular, and non-Muslims’ understanding of this phenomenon in general.